Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1007/s11837-021-04701-2
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Application of Machine Learning in Design, Synthesis, and Characterization of Metal Matrix Composites: Current Status and Emerging Applications

Abstract: In this article we provide an overview on the current and emerging applications of machine learning (ML) in the design, synthesis, and characterization of metal matrix composites (MMC). We have demonstrated that ML methods can be applied in three distinct categories, namely property prediction, microstructure analysis, and process optimization, which are associated with three major classes of ML techniques, i.e., regression, classification, and optimal control, respectively. ML algorithms have been successfull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 100 publications
0
14
0
Order By: Relevance
“…Some successful studies using ML and AI can also be found for composites with soft metals as matrix [54], for example aluminum, copper or zinc and their alloys [55][56][57][58][59]. As such, Stojanović et al [60] investigated the friction and wear behavior of aluminum hybrid composites with Al-Si alloy matrix and 10 wt.% silicon carbide (SiC) as well as 0, 1, and 3 wt.% graphite.…”
Section: Metal Matrix Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some successful studies using ML and AI can also be found for composites with soft metals as matrix [54], for example aluminum, copper or zinc and their alloys [55][56][57][58][59]. As such, Stojanović et al [60] investigated the friction and wear behavior of aluminum hybrid composites with Al-Si alloy matrix and 10 wt.% silicon carbide (SiC) as well as 0, 1, and 3 wt.% graphite.…”
Section: Metal Matrix Compositesmentioning
confidence: 99%
“…Most of the works also comprised forward ML models, which were developed to predict the tribological behavior as output based on various input parameters such as material or test conditions. In principle, however, inverse models to characterize the materials and surfaces [54] or physics-informed ML approaches [134] can also be applied. With a closer assessment of the intentions and objectives of the studies, as well as the overrepresentation of ANNs, one might get the impression that ML is in many cases being used to serve its own ends.…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%
“…This native oxide layer is highly defective and cannot provide effective protection from corrosion, especially when different types of heterogeneities are incorporated within it [ 16 , 19 , 20 , 21 , 22 ]. Therefore, the corrosion resistance of cast Al–Si alloys strongly depends on the surface condition, predominantly on the silicon content and the surface roughness [ 23 , 24 ]. The surface roughness has a significant effect on reducing the corrosion resistance, as does a change in the surface chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…The surface roughness has a significant effect on reducing the corrosion resistance, as does a change in the surface chemistry. Here, the constant trade-off between these two influential surface parameters must be considered [ 13 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation